Investigation of the Off-Label Drug Use at Provincial and Regional Levels - AKICI, AHMET (GAZI UNIV, FAC MED, 2018)
Objective: The use of drugs outside the purpose for which they are approved, e.g. different indications, doses, administration forms, age groups, or special populations etc. is called off-label drug use (OLDU). This study aimed to investigate OLDU at provincial and territorial levels in Turkey. Methods: A total of 5681 applications submitted to the Turkish Medicines and Medical Devices Agency in 2011 were investigated. These applications were examined at provincial and NUTS-1 (Nomenclature of Territorial Units for Statistics-1) levels based on age, sex, time and place of application, etc. and top five most common drugs for each region. Results: OLDU applications were submitted mainly during Quarter 2 and 81.6% of them were from university hospitals. Except for Southeastern Anatolia, the average age was >30-year in all regions and majority of patients (55.1%) were female. Applications were mostly submitted from Western Anatolia (34.9%), followed by Istanbul (26,5%) and Aegean (10,3%) regions at institutional level. The highest and lowest number of applications per 1000 specialist physician at provincial level were Cankiri (778.8) and Istanbul (20.0), respectively. While varying by rank among NUTS-1 regions, most commonly applied drugs were rituximab, mycophenolate mofetil, and iloprost trometamol. Conclusion: Rational OLDU practice depends on some critical factors including regional characteristics. This study is the first to show variations of OLDU applications at provincial and regional level, which need to be considered to improve functionality of OLDU. These findings are expected to shed light on new regulations and studies that will elucidate the causes of differences.
Keywords: Off label drug use; regional differences; NUTS-1; cities; CLINICAL-PRACTICE; THE-LITERATURE; TURKEY; PRESCRIPTIONS; NATIONWIDE; ONCOLOGY; DISEASES; GENDER; HEALTH; CARE